Second-Order Nonlinear Circular Dichroism in Square Lattice Array of Germanium Nanohelices - Saerens, Grégoire; Ellrott, Günter; Pashina, Olesia; Deriy, Ilya; Krstic, Vojislav; Petrov, Mihail; Chekhova, Maria; Grange, Rachel (ACS Photonics, 2024)
Second-harmonic generation (SHG) is prohibited in centrosymmetric crystals such as silicon or germanium due to the presence of inversion symmetry. However, the structuring of such materials makes it possible to break the inversion symmetry, thus achieving generation of second-harmonic. Moreover, various symmetry properties of the resulting structure, such as chirality, also influence the SHG. In this work, we investigate second-harmonic generation from an array of nanohelices made of germanium. The intensity of the second-harmonic displayed a remarkable enhancement of over 100 times compared to a nonstructured Ge thin film, revealing the influence of interaction between nanohelices. In particular, nonlinear circular dichroism, characterized through the SHG anisotropy factor gSHG-CD, changed its sign not only with the helix handedness but also with its density as well. We believe that our discoveries will open up new paths for the development of nonlinear photonics based on metamaterials and metasurfaces made of centrosymmetric materials.
CRIS-Team Scopus Importer:2024-08-30
Keywords: centrosymmetric crystals; circular dichroism; germanium nanohelices; inversion symmetry; second-harmonic generation